Uma abordagem de ensino de números reais - Medeiros, Jozan (2010)
This research was the development of a didactic approach in its implementation and evaluation in a class of 3rd year of high school, the purpose of developing real numbers with the goal of enabling students to acquire knowledge on the sets of numbers, both formative and functional Recommended official documents for basic education, plus a teaching module, containing texts, educational activities, methodology and a proposal for evaluation. From the assumption that students have difficulties in articulating the different sets of numbers, both in relation to cognitive aspects such as the representational, this approach was developed following the model suggested by Ulrich Christiansen, who uses the line number as the context articulator, enriched with situations and problems of mathematical history, seeking to associate numbers to geometry and algebra. The results of the implementation of educational module was analyzed using the students' participation in the activities performed during the didactic analysis of data obtained from a pretest and a posttest on the cognitive domain and representational of the students, as well as by direct observations, indicating its suitability to the proposed objectives.